If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + 5) + -1(9x + -4) = 0 Reorder the terms: (5 + 3x) + -1(9x + -4) = 0 Remove parenthesis around (5 + 3x) 5 + 3x + -1(9x + -4) = 0 Reorder the terms: 5 + 3x + -1(-4 + 9x) = 0 5 + 3x + (-4 * -1 + 9x * -1) = 0 5 + 3x + (4 + -9x) = 0 Reorder the terms: 5 + 4 + 3x + -9x = 0 Combine like terms: 5 + 4 = 9 9 + 3x + -9x = 0 Combine like terms: 3x + -9x = -6x 9 + -6x = 0 Solving 9 + -6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -6x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -6x = 0 + -9 -6x = 0 + -9 Combine like terms: 0 + -9 = -9 -6x = -9 Divide each side by '-6'. x = 1.5 Simplifying x = 1.5
| p-0.20p=5 | | 2(1a+2a)= | | (8x+7)-(9x-8)= | | 21=3t | | 3ax-2=5ax-1 | | -3d+5+d15= | | f(x)=6xln(2x)-6x | | 11=-5g-2 | | (3x-1)(10x-3)=0 | | 3x+3(6x-12)=132 | | 3r-4rs+2s= | | 0.07=56 | | 72=9g | | 2X-21+3X-34=180 | | -4(5x+2)+3(x-3)= | | 2w-3(3w+5)=3w+5 | | -8x-5y=15 | | 35-19=3(x-3) | | ?(2x-4)+5=-?(x+1) | | 3x^3+13x^2-16=0 | | 48x^2-16x-20=0 | | -138-6(6b-7)= | | 2n-1=-11 | | 4x+8y=52 | | 3n-8=-20 | | 4x-10=12+4(x+8) | | 2-c=29 | | ?(2x-4)=-?(x+1) | | 4t-1=5(t+5) | | 3x=7x+20 | | 5(6+3r)+7127= | | 13mn-5nm+2mn= |